lim

x->0 sinx secx / x

use the fact that the limit as x approaches 1 of (sinx / x) = 1

Similar Questions
  1. Prove the following:[1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)]
    1. answers icon 3 answers
  2. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
    1. answers icon 0 answers
  3. how do i simplify (secx - cosx) / sinx?i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx) and then i
    1. answers icon 1 answer
more similar questions